Psychometric Evaluation of the Electronic Pain Assessment Tool: An Innovative Instrument for Individuals with Moderate-to-Severe Dementia - Atee, M.; Hoti, Kreshnik; Hughes, J. (S. Karger AG, 2018)
© 2018 S. Karger AG, Basel Background/Aims: Pain is common in aged care residents with dementia; yet it often goes undetected. A novel tool, the electronic Pain Assessment Tool (ePAT), was developed to address this challenging problem. We investigated the psychometric properties of the ePAT. Methods: In a 10-week prospective observational study, the ePAT was evaluated by comparison against the Abbey Pain Scale (APS). Pain assessments were blindly co-performed by the ePAT rater against the nursing staff of two residential aged care facilities. The residents were assessed twice by each rater: at rest and following movement. Results: The study involved 34 residents aged 85.5 ± 6.3 years, predominantly with severe dementia (Psychogeriatric Assessment Scale – Cognitive Impairment score = 19.7 ± 2.5). Four hundred paired assessments (n = 204 during rest; n = 196 following movement) were performed. Concurrent validity (r = 0.911) and all reliability measures (? w = 0.857; intraclass correlation coefficient = 0.904; a = 0.950) were excellent, while discriminant validity and predictive validity were good. Conclusion: The ePAT is a suitable tool for the assessment of pain in this vulnerable population.